2014
DOI: 10.7557/2.34.1.2572
|View full text |Cite
|
Sign up to set email alerts
|

Population characteristics, space use and habitat selection of two non-migratory caribou herds in central Alaska, 1994 - 2009

Abstract: Conservation and management of Alaska's caribou (Rangifer tarandus granti) herds are important for ecological, cultural, social, and economic reasons. While most research is directed towards the large migratory herds, smaller herds that may or may not be migratory can be an equally valuable component of the state's faunal resources; but for many of these smaller herds, basic information on herd size, demographics, space use and movements is lacking. We compiled Very High Frequency (VHF) telemetry data collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Alaska includes over 30 herds of caribou distributed throughout the state, although many of these are smaller herds that undertake only local migrations or none at all [29]. Four large migratory herds range across the Brooks Range in northern Alaska.…”
Section: Introductionmentioning
confidence: 99%
“…Alaska includes over 30 herds of caribou distributed throughout the state, although many of these are smaller herds that undertake only local migrations or none at all [29]. Four large migratory herds range across the Brooks Range in northern Alaska.…”
Section: Introductionmentioning
confidence: 99%
“…Harzel et al (2006) suggested that displaying RSF results as a continuous surface can be misleading and RSF values should be reclassified, or binned, for map creation to provide honest and relevant predications. However, there has been minimal discussion on the most appropriate binning methods, and displaying RSF values as a continuous surface remains common (Brook & McLachlan, 2009; Dellinger, Proctor, Steury, Kelly, & Vaughan, 2013; Dugal et al, 2013; Fortin et al, 2008; Horne et al, 2014; Teichman, Cristescu, & Nielsen, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…We tested for overall differences in individual selection coefficients between males and females with multivariate analysis of variance (MANOVA) using the PillaiBartlett statistic (Horne et al, 2014). If there were no significant differences (P<0.05) in selection coefficients between sexes, we averaged the selection coefficients across individuals to generate population-level estimates.…”
Section: Modelling Home Range and Habitat Selection Simultaneouslymentioning
confidence: 99%
“…The synoptic model structure is based on a weighted distribution used to predict a species' probability of use of a given area based on an individual's space use (i.e., home range) and the habitat features that influence their space use (Horne et al, 2014).…”
Section: Modelling Home Range and Habitat Selection Simultaneouslymentioning
confidence: 99%